Penggunaan Pay Later di E-commerce Shopee Menurut Hukum Islam - Savitri, Erin Dewi (Journal of Law, Society, and Islamic Civilization, 2023)
This research examines the problem of using Pay Later in buying and selling online and imposing fines for late payment of Pay Later bills on E-commerce Shopee using Islamic Law. The use of Pay Later is a new muamalah and the law is unclear, due to the interest required at the beginning. This study aims to find out the views of Islamic law on buying and selling transactions using Pay Later on E-commerce Shopee and knowing the views of Islamic law on fines for late payment of Pay Later bills on E-commerce Shopee. The research results obtained are that the practice of buying goods at Shopee using the Shopee Pay Later payment method is not allowed or is considered illegal because the practice of debt between buyers and Shopee contains interest or benefits received by Shopee, this is called Riba Qardhh. The imposition of late fines in the practice of buying and selling using Shopee Pay Later is not in accordance with Islamic law because there is an additional nominal amount to the debt, so the law is unlawful, this is called Riba Jahiliah.